PWE-152 Primary Sclerosing Cholangitis-inflammatory Bowel Disease Is Associated With An Increased Frequency Of Post-transplant Colonic Lymphoma. (9th June 2014) - Trivedi, PJ; Wright, T; Robinson, J; Li, K-K; Gunson, B; Adams, D; Ferguson, J; Hirschfield, G
Abstract : Introduction: Post-transplant lymphoproliferative disease (PTLD) is a recognised complication of liver transplantation (LT). Although small intestinal involvement is common, factors predisposing to colonic disease are not well characterised. Methods: A case-note review of all patients undergoing liver transplantation (1982–2013) was performed, and subsequently cross-referenced with an institutional lymphoma database comprising all biopsy-proven PTLD cases to date. Putative risk factors for development of colonic lymphoma were analysed using SPSSv21. Results: Over a 31-year adult 'first liver' transplant experience (No. of recipients=2872), 72 cases of post-LT lymphoproliferative disease were identified and most commonly observed in the context of primary biliary cirrhosis (PBC; n = 20) and primary sclerosing cholangtitis (PSC; n = 14). Overall, intestinal involvement was observed in 18/72 patients, representing predominantly small bowel disease (n = 12). Colonic lymphoma occurred only in individuals transplanted for PSC (n = 6; median 5.0yrs post-transplant; IQR: 3.2–11.7), all of who had underlying colitis. In all cases, disease was a diffuse large B-cell lymphoma; however, only 2 patients had EBV-(LMP)-positive tumours, from which only 1 a detectable serum EBV-titre (qPCR). There were no significant associations with age at transplantation, male gender, treatment with azathioprine or tacrolimus, duration of azathioprine or calcineurin inhibitor exposure, or onset of colitis post-LT. Only one patient (each) with PTLD occurring in the context of cardiothoracic (n = 6) and renal (n = 32) transplantation developed large bowel disease, and under these circumstances was part of a disseminated lymphomatous process. Conclusion: PSC/colitis is associated with development of colonic lymphoma post-LT. Additional risk factors have yet to be identi, UKfied. Disclosure of Interest: None Declared.